UPAYA PENINGKATAN HASIL BELAJAR DAN KEAKTIFAN PADA MATERI MUSYAWARAH MELALUI MODEL THINK PAIR SHARE KELAS III SD NEGERI LOANO TAHUN AJARAN 2023/2024 - Agustina Sri Wulandari; Suyoto; Arum Ratnaningsih (LPPM STKIP Bina Bangsa Meulaboh, 2024)
Research has been conducted entitled Efforts to increase learning outcomes and activity in deliberation material through the Think Pair Share Model for Class III Loano State Elementary School for the 2023/2024 academic year, which aims to determine whether there is an increase in learning outcomes and activity in deliberation material using the think pair share learning model. This research design uses a type of classroom action research (PTK) with two cycles. The research subjects were class III students at Loano State Elementary School. Data collection techniques used include interviews, observation, tests and documentation. The results of this research show that implementing the think pair share model can increase student activity and learning outcomes. In the pre-cycle stage it got 38%, cycle I rose to 60.4%, and cycle II rose to 91.56%. This can be interpreted as saying that the think pair share model is active or has experienced an increase in percentage of 31.16%. Meanwhile, the learning outcomes of students in the deliberation material in cycle I obtained an average of 59.5 from 26 students who took the evaluation test and in cycle II obtained an average of 86 from 26 students who took the evaluation test. So student learning outcomes experienced an average increase from cycles I and II of 26.5. Thus, the application of the think pair share model can increase student activity and learning outcomes in class III deliberation material at Loano State Elementary School for the odd semester of the 2023/2024 academic year.